1996
DOI: 10.1109/23.506650
|View full text |Cite
|
Sign up to set email alerts
|

Performances of SI GaAs detectors fabricated with implanted ohmic contacts

Abstract: The slow component of the output pulse of Semi-Insulating (SI) Gallium Arsenide (GaAs) particle detectors, which affects charge collection efficiency (cce), has been generally attributed to trapping/detrapping effects. However, most of the detectors analyzed in the literature can only be operated below the voltage v d necessary to extend the electric field all the way to the ohmic contact, making difficult to distinguish between the effect of the non-active part of the detector and that of trapping/detrapping.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Indeed, due to their very low free charge carrier concentration n 10 7 cm À3 , for many years Schottky diodes fabricated on SI GaAs were assumed to be fully depleted, even at zero bias voltage. The ohmic contacts have been realized on the whole back surface of the wafers by implanting Si ions [9]. It was also found that the depletion layer width W does not increase with the square root law valid for Schottky junctions on semiconducting materials, even if no identity of opinions on the functional relationship between W with biasing V a was reached for a long time.…”
Section: Obic Analyses Of Semi-insulating Gallium Arsenidesupporting
confidence: 87%
“…Indeed, due to their very low free charge carrier concentration n 10 7 cm À3 , for many years Schottky diodes fabricated on SI GaAs were assumed to be fully depleted, even at zero bias voltage. The ohmic contacts have been realized on the whole back surface of the wafers by implanting Si ions [9]. It was also found that the depletion layer width W does not increase with the square root law valid for Schottky junctions on semiconducting materials, even if no identity of opinions on the functional relationship between W with biasing V a was reached for a long time.…”
Section: Obic Analyses Of Semi-insulating Gallium Arsenidesupporting
confidence: 87%
“…For the case of ␣ particles ͑5.48 MeV͒, the presence of plasma effects due to the high density of generated pairs (10 18 cm Ϫ3 ) ͑Ref. 9 On the basis of the above simulations, we provide a microscopic interpretation of measured charge signals. 8 This delay is not of primary interest in the present letter where we mostly focus on long-time-scale effects ͑above 10 ns͒.…”
Section: ͓S0003-6951͑98͒04438-6͔mentioning
confidence: 93%
“…The improved ohmic contact was realised by annealing a multi-layer titaniumpalladium-germanium metal contact. Alenia SpA have fabricated diodes with an ion-implanted ohmic contact which allow a bias many times V f d to be applied [4].…”
Section: Understanding Gaas Detectorsmentioning
confidence: 99%